The Returns to STEM Programs for Less-Prepared Students - Riehl, Evan; Ng, Kevin (American Economic Journal: Economic Policy, 2024)
The returns to selective STEM programs depend on whether students complete these programs, earnings conditional on completion, and counterfactual schooling choices. Much research has focused on only one of these margins, potentially leading to an incomplete picture of the returns to STEM education for students with less academic preparation. Using data from a Colombian University and two empirical strategies, we find less-prepared students have higher earnings returns to selective STEM programs than more-prepared students, even though they are less likely to complete these programs. A key mechanism is that less-prepared students have lower-paying counterfactual schooling options.
Keywords: Human Development; Income Distribution; Labor Productivity, Wage Level and Structure; Research Institutions; Higher Education; Higher Education